The Real Possibility of Competitive Generation Markets in Hydro Systems : The Case of Brazil - Estache, Antonio; Rodriguez-Pardina, Martin (World Bank, Washington, DC, 2012)
Brazil's electricity sector is made up of more than sixty-five, mostly vertically integrated, federally- and state-owned monopolies. The most pressing problems in the sector are excessive operational costs and large investment needs. Both of these problems can be addressed through more competition and more private participation. There is a consensus among federal and state policymakers and key operators that the sector's potentially competitive segments should be separated from its natural monopoly segments and awarded as concessions or sold to private investors. However, there are important technical challenges, one of which relates to competitive generation. First, to ensure open entry and the long-term viability of competition in the electricity sector, the government must figure out how to competitively allocate water rights. Second, to provide incentives for investing in generating capacity, a pricing system must be put in place that will ensure recovery of the high sunk capital costs characteristic of hydro systems. This Note describes one consistent approach, using incentive-based organization and regulation, for overcoming the technical challenges to effective competition in the generation market.